Serum sTREM‐1 level is quite higher in Crimean Congo Hemorrhagic Fever, a viral infection. Issue 9 (25th February 2016) - Altay, Fatma Aybala; Elaldi, Nazif; Şentürk, Gönül Çiçek; Altin, Nilgün; Gözel, Mustafa Gökhan; Albayrak, Yurdagül; Şencan, İrfan
Abstract : Members of triggering receptor expressed on myeloid cells (TREM) family are known as immunmodulators in several infectious or noninfectious inflammatory disorders. The information about their role in viral infections is very limited. To enlighten if there is a relation between soluble TREM‐1(sTREM‐1) and a viral infection, Crimean Congo Haemorrhagic Fever (CCHF), we investigated the levels of sTREM‐1 in the sera of 39 CCHF patients both at admission and at recovery and compared with 40 healthy controls by using microELISA technique. Statistical analysis was made by using Statistical Package for Social Sciences (SPSS) for Windows 20 programme. Value of P  < 0.05 was accepted as significant for statistical analyses. Median sTREM‐1 level was higher in CCHF group when compared to the control group (1, 961 vs. 151.1 pg/ml, respectively; P  < 0.001). In CCHF patients, sTREM‐1 levels were significantly decreased at recovery compared to initial level measured at hospital admission (1, 961 vs. 948 pg/ml, respectively; P  = 0.019). ΔsTREM‐1 is correlated with ΔCRP, ΔWBC, and ΔPlt. We found that serum levels of sTREM‐1 higher than 405.9 pg/ml existed as a cut off point for differentiating CCHF patients and control group with a sensitivity of 94.9% and specifity of 87.5%. It is proved that sTREM‐1 is increased and correlates with the clinical and laboratory findings in CCHF, a viral infection characterized by activation of inflammation. This finding may lead new studies to enlighten the pathogenesis of infections developing by activation of inflammatory cascades and high level cytokine releases, especially. J. Med. Virol. 88:1473–1478, 2016 . © 2016 Wiley Periodicals, Inc.